Peningkatan Kesadaran Memperbaiki Mood pada Mahasiswa di Usia Dewasa Awal melalui Refleksi dan Jurnaling - Galuh Laily Agustin; Afrilia Nur Fadhila; Khairunisa Azra Amalina; Nur Sahlami; Aliya Febriyanti; Dewi Yanah; Nazmi Laila Gita; Rohman; Muhamad Ahyudin; Muhamad Fahri Darmawan (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Students in early adulthood often face academic, social, and personal pressures that cause fluctuations in mood and affect mental health and psychological well-being. The main issue addressed in this study is students’ low ability to recognize, understand, and manage emotions adaptively, highlighting the need for effective strategies to enhance emotional awareness. This research investigates the effectiveness of self-reflection and journaling in improving students’ mood awareness. A combination of descriptive qualitative and quasi-experimental pretest-posttest designs was used, with instruments including mood scales, reflection guidelines, and students’ daily journals. Results showed a 32% increase in the average mood awareness score, a decrease in students with low awareness from 64% to 18%, and an increase in high awareness from 14% to 56%. Active participation was observed in 78% of students, while 85% consistently documented their emotional experiences, 88% reported feeling relieved, and 76% could identify recurring emotional patterns. The intervention also promoted the development of more adaptive self-regulation strategies, such as time management, adequate rest, and social support, increasing from 21% before the intervention to 69% afterward. Sustainability of practice was indicated by 61% of students intending to continue journaling independently and 57% integrating it into their daily routines. The novelty of this study lies in the integration of self-reflection and journaling as a practical, systematic, and sustainable approach to enhance emotional awareness and psychological well-being. The findings confirm that a simple yet structured intervention can create significant improvements in emotion management and adaptive behaviors among students.